Proposed Agreement with the Cities of Oxnard and Camarillo Regarding Airport - Loren W. Enoch:::::: (1971)
A letter from the County Executive Loren Enoch informing the Board of Supervisors of the opinion of the County of Ventura, County Counsel, and the Director of Airports and Harbor regarding an agreement between Oxnard and Camarillo.